Pengaruh Latihan Static Cycle Terhadap Peningkatan Volume Oksigen Maksimal (Vo2max) Pada Pasien Pasca Stroke - Ashadi, Arjun Gholpa; , Isnaini Herawati, SSt. FT, M. Sc; , Umi Budi Rahayu, SSt. Ft. SPd. M. Kes (2016)
To know the effect of cardiovascular exercise to increase the maximum volume of oxygen (VO2max) in patients with post-stroke. Fitness patients with post-stroke can be achieved through a variety of exercises, especially exercises are aerobic routine and controlled with the right dose, such as gymnastics, cycling and walking on a treadmill, with these exercises is expected durability of cardiorespiratory will always be controlled and optimized so post-stroke patients can resume their daily lives with the maximum without significant complaints so cardiorespiratory endurance will be maintained